UMP making a mark in education - UMP, PNC (2022)
KUANTAN: Universiti Malaysia Pahang (UMP) is continuing to strengthen its role as a technology university as part of the Malaysian Technical University Network to boost the country's technical and vocational training and education (TVET) empowerment agenda.